(untitled) (Zaporizhzhia Historical Review, 2021)
The article finishes the circle of author’s publications devoted to the history of anarchists’ emigration at the beginning of XX century. It is examined the specification of anarchists’ activity in Europe and North America in the conditions of the war. It defines the anarchists’ attitude to the war. Special attention is paid to the analysis of the contents of anarchists’ periodical publications. Scholar determines the role of emigration in preservation of Russian anarchism as a political trend.